The Impact of The Digital Economy on Achieving The Efficiency of The General Budget: A Study in Reforming The Iraqi Economy: Dampak Ekonomi Digital dalam Mencapai Efisiensi Anggaran Umum: Sebuah Studi tentang Reformasi Ekonomi Irak - Roa'a Mohammed Kadhim (Academia Open, 2024)
The Iraqi economy operates with a large number of variables and seeks through them to achieve economic goals of economic growth, full employment, economic stability, reducing inflation and other goals, and this is done through macroeconomic policies, monetary and financial. The problem for the budget system is embodied in the urgent need for reform and development that includes the preparation and implementation of a model budget in a way that can enhance the ability and resilience of the financial and economic system to confront economic crises in a technologically advanced environment, where technological development is represented by the digital economy as a transformative force, embodying the convergence of technology and the Internet in shaping a new scene of economic activity, which includes a wide network of companies, institutions and individuals who use digital technologies and the Internet to create, exchange and consume goods, services and information. The digital economy is essentially based on data as the blood that feeds innovation and decision-making trends Highlights: Iraqi economy aims for growth via macroeconomic, monetary, and financial policies. Budget reform crucial for resilience in a tech-driven, digital economy. Data fuels innovation, shaping decision-making in economic activities. Keywords: Digital economy, General Budget, Efficiency, Iraqi Economy